Comparative Immunogenicity of the Recombinant Receptor-Binding Domain of Protein S SARS-CoV-2 Obtained in Prokaryotic and Mammalian Expression Systems - Merkuleva, Iuliia A.; Shcherbakov, Dmitry N.; Borgoyakova, Mariya B.; Shanshin, Daniil V.; Rudometov, Andrey P.; Karpenko, Larisa I.; Belenkaya, Svetlana V.; Isaeva, Anastasiya A.; Nesmeyanova, Valentina S.; Kazachinskaia, Elena I.; Volosnikova, Ekaterina A.; Esina, Tatiana I.; et al. (Vaccines (Basel), 2022)
The receptor-binding domain (RBD) of the protein S SARS-CoV-2 is considered to be one of the appealing targets for developing a vaccine against COVID-19. The choice of an expression system is essential when developing subunit vaccines, as it ensures the effective synthesis of the correctly folded target protein, and maintains its antigenic and immunogenic properties. Here, we describe the production of a recombinant RBD protein using prokaryotic (pRBD) and mammalian (mRBD) expression systems, and compare the immunogenicity of prokaryotic and mammalian-expressed RBD using a BALB/c mice model. An analysis of the sera from mice immunized with both variants of the protein revealed that the mRBD expressed in CHO cells provides a significantly stronger humoral immune response compared with the RBD expressed in E.coli cells. A specific antibody titer of sera from mice immunized with mRBD was ten-fold higher than the sera from the mice that received pRBD in ELISA, and about 100-fold higher in a neutralization test. The data obtained suggests that mRBD is capable of inducing neutralizing antibodies against SARS-CoV-2.